Propuesta De Un Programa Basado En El Desarrollo De Habilidades Y Actitudes Para El Mejoramiento De La Adaptación Frente A La Reubicación Laboral De Oficiales Y Suboficiales Victimas Del Combate A Nivel Físico Y Psicológico (2018)
The labor relocation in the National Army takes on a great relevance that has a high percentage in terms of officers and NCOs who are injured in the combat area that results in some type of physical disability with emotional and psychological affectation. For this reason, this project will focus on designing a proposal that allows knowing the capacities for the development and adaptation of the labor relocation within the National Army, based on the training and guidance that should be offered to the military in front of its new role within the institution.